Technical Indicators and Assessment of Energy Expenditure Indifferent Tillage Methods and Planting Wheat - Mahmood Kaboli (Journal of Global Pharma Technology, 2017)
The objective of this work was to study the effects of tillage and planting methods on technical indicators, energy and other properties. In this research, which was carried out in khatam area in 2014-2015, different tillage and planting methods included conventional tillage, conservation tillage by chisel plow, conservation tillage by combined plow and no tillage based on randomized complete block design with three replication? Factors that were used as a measure of comparison, include the average number of plants per square meter, uniform planting depth (vertical distribution uniformity of seeds), a uniform distribution of seeds (uniform distribution of seed surface), the percentage of green seeds, the measurement of time the actual capacity and practical calculation tools, power tools and fuel energy consumption in any way. The results of this research, no tillage with fuel consumption of 15 liters per hectare, the lowest fuel consumption and therefore less fuel energy of 671 MJ, most stored soil moisture 30.4 percent, the lowest since the 33/67 minutes per hectare and thus the maximum capacity of the machine's actual position was higher than the other treatments. Conventional tillage with the highest fuel consumption of 47 liters per hectare fuel consumption rate, the lowest percentage of soil moisture 61/20% and a maximum operating time of 33/295 minutes per hectare respectively.Keywords: Tillage methods, Energy, Wheat, Fuel.